TEACHING AND LEARNING PERFORMANCE: THE PERCEPTION OF THE CERTIFIED ENGLISH TEACHERS - Irna Ningsih; Machdalena Vianty; Rita Inderawati (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: This study was aimed at investigating the perception of the certified teachers of English toward their teaching and learning performance by finding out the most dominant indicators of performance in terms of planning and preparing, conducting learning process, and learning evaluation. This was a survey study involving seventy nine certified teachers of English at twenty two public senior high schools in Palembang. The data were obtained through a set of questionnaire. The percentage analysis was used as the technique for data analyses. The result of this study showed that the certified teachers of English tended to maintain their teaching and learning performance based on different dominant indicators based on their own professional development as certified teachers.It is suggested that the teachers (1) improve their competence which already represented through every indicators of teachers’ performance; (2) implement the theoretical knowledge they gained during certification into their teaching practices in classroom. Key words: perception; teaching and learning performance; certified teachers of English